The Influence of Psychological and Social Factors on Patients' Decisions to Visit with Brand Image as an Intervening Variable in Outpatient Patients at Hermina Hospital, Depok - Shindy Kurnia Putri; Endang Ruswanti; Johannes Johannes (Inovasi Kesehatan Global, 2025)
This study is based on the results of initial observations that indicate a downward trend in the number of non-JKN outpatients. In January 2024, the achievement was only 415 of the target of 596 visits (69.6%), the achievement was again not in accordance with the target in September with 92.8%. The purpose of this study was to examine the effect of psychological factors and social factors on patient decisions to visit with brand image as an intervening variable in outpatients at Hermina Hospital, Depok. This type of research is quantitative with a causality design. The population is outpatients at Hermina Hospital, Depok. The results of the distribution through questionnaires obtained 130 respondents according to the minimum sample set. The analysis technique used the three box method analysis and SEM-PLS. The results of the study showed that psychological factors, social factors, and brand image simultaneously had a significant effect on patients' visit decisions, with a contribution of 67.8%. Both psychological and social factors influenced brand image and patients' visit decisions. Brand image also had an effect on patients' visit decisions. Among the three variables, brand image was the most dominant in increasing patients' visit decisions.